DYSFUNCTION OF MODERN RUSSIAN INSTITUTES OF STATE AWARDS IN THE SPHERE OF EDUCATION AND SCIENCE - Aleksey V. Ruchkin (Russian State Vocational Pedagogical University, 2015)
The purpose of the study is to analyze the main dysfunctions of the Russian premium institutes in the field of education and science, and to find out its leveling instruments, by examining the experience of foreign countries; to identify the basic requirements for the novitiate for state awards to employees of education and science in modern Russia in comparison with foreign countries. Methods. Neo institutional approach is used by the author. Methods involve comparative analysis, cross-national analysis, and classification. The original solution of tasks associated with the use of a single system-approach to the sociological study of state awards in the sphere of education and science, is extrapolated from institutional economics. Results. The basic approaches to the determination of the nature and functions of awards institutions in the field of education and science are considered; its relationship with other social, economic and political trends of contemporary politics in Russia is noted. The basic conditions of non-material motivation of workers of scientifically-educational area in modern Russia in comparison with other countries, including the post-Soviet territory states are defined. Both officially established rules and other requirements to candidates on reception of the state honourable distinctions, observed with the Soviet period are considered. The study identifies the main factors that influence the perception of the role of changes in modern society awards, offers solutions to the identified problems. Scientific novelty. The critical analysis of working rules of the Russian legislation regulating an order (procedures) of rewarding has allowed to reveal major disadvantages of the Russian institute of the state awards: opacity of estimated judgements considering the work of the applicant for the award; absence of accurate hierarchy of the state awards and quantity indicators at measurement of merits and results of activity; value of awards loss in the opinion of a society and separate citizens, etc. Ways of the solution of the revealed problems are offered. In particular, the author points out that it is necessary to create an incentive system intended not only for remote prospect (for example, upon reaching a pension age), but also for the current labour period; material remuneration should be a sufficient impulse for professionals and based on a recognition of achievements, first of all, by colleagues (of the same profession), not unauthorized people. It is necessary to work out quantity indicators for an estimation of activity of educators and academics. Introduction of the structured requirements to this activity is to make objective process of representation to the state awards and will generate professional work standards. Moreover, it is necessary to lower qualifications on presence of the certain experience and to remove some other restrictions for the state recognition. Practical significance. According to the author's analysis, the reduction of dysfunctions of the Russian premium institutes will allow to return retention feature in the sphere of education and sciences of the most valuable personnel; to involve «a fresh creative power» in the given field of work; to create reference points of professional growth for working teachers and scientists; to generate the potential workers concepts of high social value and the importance of professional work in an educational sphere and science.